Effectiveness Of Geography Teaching Materials Based On Disaster Literacy To Improve Disaster Preparadness - Ramadhan, Ulfah Khairani; Sarwono, Sarwono; Muryani, Chatarina (Universitas Sebelas Maret, 2020)
Disaster literacy is integrated in learning in schools such as designing teaching materials that contain disaster literacy in it so that participant preparedness students in dealing with disasters can increase, the purpose of this study is to determine the effectiveness of the use of geography teaching materials based on disaster literacy to improve the readiness of Kerjo Karanganyar high school students in dealing with landslides. The method used in this study is one group pre-test post-test, using the t test analysis or independent sample t test with a confidence level of 5%, the results of the study are as follows the effectiveness of the use of geography-based disaster literacy teaching materials at a 5% confidence level (0 , 05) obtained sig 0.0046 <0.05 which means there is an increase in students' disaster preparedness in all aspects, namely knowledge, attitudes, emergency response plans, disaster warning systems and resource mobilization capabilities.